2022
DOI: 10.1002/pros.24342
|View full text |Cite
|
Sign up to set email alerts
|

PLK4 is upregulated in prostate cancer and its inhibition reduces centrosome amplification and causes senescence

Abstract: Background Identification of novel molecular target(s) is important for designing newer mechanistically driven approaches for the treatment of prostate cancer (PCa), which is one of the main causes of morbidity and mortality in men. In this study, we determined the role of polo‐like kinase 4 (PLK4), which regulates centriole duplication and centrosome amplification (CA), in PCa. Materials and Methods Employing human PCa tissue microarrays, we assessed the prevalence of CA, correlated with Gleason score, and es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
(107 reference statements)
2
11
0
Order By: Relevance
“…----------------------------------------------------- A previous study indicated that both DFS and OS rates were reduced in patients with non-small cell lung cancer with high PLK4 expression compared with patients with low PLK4 expression (14). Similarly, the present study revealed that high PLK4 expression was partially associated with poor survival in patients with RCC, which could be explained by PLK4 facilitating excessive centrosome amplification (15). The latter could induce the metastatic potential and invasion of tumor cells, which in turn may result in poor survival of patients with RCC (34).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…----------------------------------------------------- A previous study indicated that both DFS and OS rates were reduced in patients with non-small cell lung cancer with high PLK4 expression compared with patients with low PLK4 expression (14). Similarly, the present study revealed that high PLK4 expression was partially associated with poor survival in patients with RCC, which could be explained by PLK4 facilitating excessive centrosome amplification (15). The latter could induce the metastatic potential and invasion of tumor cells, which in turn may result in poor survival of patients with RCC (34).…”
Section: Discussionsupporting
confidence: 73%
“…PLK4 is located on human chromosome 4q27-28 and has been reported to modulate centriole duplication, which affects cancer invasion and metastasis (25). Previous studies have detected its expression in various solid tumors, including those of the bladder and prostate (15,18). For example, a previous study has demonstrated elevated PLK4 expression in human prostate cancer cell lines and tumor tissues derived from patients with prostate cancer (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that PLK4 was high expressed in several human cancers, including hepatocellular carcinoma, colorectal cancer, gastric cancer, glioblastoma, neuroblastoma, breast cancer, and lung cancer ( Zhang et al, 2021 ), and had a close relationship with the progression of cancers. Due to the vital roles of PLK4 in the regulation of centrosome replication and the pathology of cancers, more and more PLK4 inhibitors were developed, such as Centrinone, Centrinone-B, CFI-400495 and YLT-11 ( Mason et al, 2014 ; Wong et al, 2015 ; Kawakami et al, 2018b ; Denu et al, 2018 ; Lei et al, 2018 ; Kerschner-Morales et al, 2020 ; Zhao et al, 2021 ; Singh et al, 2022 ). The already known studies information about above PLK4 inhibitors, such as structures, mainly studied cancer cells and effects of these inhibitors on the biological behaviors have been summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%